O currículo dos cursos técnicos de lazer no Brasil: um estudo de caso da formação profissional - Carla Augusta Nogueira Lima e Santos (2011)
The possibilities of professional training in leisure have been growing and, as a consequence, different curriculums have been proposed. Considering leisures expansion and its possibilities of performance, many trainings have been created to enable leisure professionals as a means to meat the makets demand. The types of courses can vary between: qualification, extension, technical, technological, undergraduation and graduation. However, this research foccused on technical courses and it intended to diagnose and analyse the profile of professional training by doing a study case of the Centro de Educação Profissional do Amapá (CEPA) wich offers a technical course in leisure. In an attempt of understanding the curriculums goals and which influences has it suffered while being made, I tried to identify how they dealt with leisure and which knowledge and competences were emphasized. The methodology used combined literature, documentary and field research. The first addressed the themes: curriculum, professional education and leisure. The documentary research was based on the analyses of the Political Pedagogical Projects of the institution (PPP-CEPA) and the course (PPP-leisure). For the field research the technique used was semi-structured interviews with nine teachers and with the coordinator of the leisure technical course. The data collected was treated based on Content Analyses using these categories: Curricular structure: organization, modifications and operation; Desired professional profile; Faculty profile; Leisure concept and the conception about professional acting in leisure and the relations between theory and practice. These reflections enabled to see the curriculum beyond its contents, goals and methodologies, identifying which political, economical and cultural matters, besides the geographical location of the city Macapá-AP, influence the concerned curriculum. With the analyses I noticed that CEPA presents as a goal the idea of training leisure technicians to meet the markets demand, however, it was also possible to notice that the approach used in leisure is not restricted to the concept of commodity to be consumed. Consequently, a concern about producing and providing knowledge beyond technical competences was identified as an attempt to form students as citizens. Likewise, I believe there is a concern that the actions of leisure professionals can go beyond mere performance, focusing also on planning and evaluating. The profile of the graduated professional contemplates theoretical and practical knowledge in a multidisciplinary way as an attempt to qualify students to act in different spaces where leisure can be experienced. The incentive to researching and the cultural formation of individuals, although being highlighted as important, might not happen due to the reduced courses schedule (840 hours). CEPA values learning through hands on method and the reduced time for training ends up prioritizing teaching strategies that focus on problem resolution, approaching competences and abilities to reality. So, the concerned study arises as a possibility of expanding the discussions, helping the comprehension of professional training in leisure and stimulating group actions in building curriculums for technical leisure courses. We hope that the gaps left here can work as new possibilities for broadening and deepen the studies about leisure and its relations with professional training.